C-reactive protein at discharge and 1-year mortality in hospitalised patients with acute decompensated heart failure: an observational study. Issue 12 (29th December 2020) - Nishimoto, Yuji; Kato, Takao; Morimoto, Takeshi; Yaku, Hidenori; Inuzuka, Yasutaka; Tamaki, Yodo; Yamamoto, Erika; Yoshikawa, Yusuke; Kitai, Takeshi; Taniguchi, Ryoji; Iguchi, Moritake; Kato, Masashi; et al.
Abstract : Objectives: To examine the association of a high C-reactive protein (CRP) level at discharge from an acute decompensated heart failure (ADHF) hospitalisation with the 1-year clinical outcomes. Design: A post-hoc subanalysis of a prospective cohort study of patients hospitalised for ADHF (using the Kyoto Congestive Heart Failure (KCHF) registry) between October 2014 and March 2016 with a 1-year follow-up. Setting: A physician-initiated multicentre registry enrolled consecutive hospitalised patients with ADHF for the first time at 19 secondary and tertiary hospitals in Japan. Participants: Among the 4056 patients enrolled in the KCHF registry, the present study population consisted of 2618 patients with an available CRP value both on admission and at discharge and post-discharge clinical follow-up data. We divided the patients into two groups, those with a high CRP level (>10 mg/L) and those with a low CRP level (≤10 mg/L) at discharge from the index hospitalisation. Primary and secondary outcome measures: The primary outcome measure was all-cause death after discharge from the index hospitalisation. The secondary outcome measures were heart failure hospitalisations, cardiovascular death and non-cardiovascular death. Results: The high CRP group and low CRP group included 622 patients (24%) and 1996 patients (76%), respectively. During a median follow-up period of 468 days, the cumulative 1-year incidence of the primary outcome was significantly higher in the high CRP group than low CRP group (24.1% vs 13.9%, log-rank p<0.001). Even after a multivariable analysis, the excess mortality risk in the high CRP group relative to the low CRP group remained significant (HR, 1.43; 95% CI, 1.19 to 1.71; p<0.001). The excess mortality risk was consistent regardless of the clinically relevant subgroup factors. Conclusions: A high CRP level (>10 mg/L) at discharge from an ADHF hospitalisation was associated with an excess mortality risk at 1 year. Trial registration details: https://clinicaltrials.gov/ct2/show/NCT02334891 (NCT02334891 ) https://upload.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000017241 (UMIN000015238).